1985
DOI: 10.1139/v85-165
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the product from the reduction of permanganate ion by trimethylamine in aqueous phosphate buffers

Abstract: The product obtained from the reduction of potassium permanganate by trimethylamine in aqueous phosphate buffers has been identified as a soluble form of colloidal manganese dioxide which is stabilized in solution by adsorption of phosphate ions on its surface. The dependence of the rate of flocculation on several experimental variables has been studied. Phosphate ions have been found to increase the solubility of the colloid by increasing the apparent energy of activation of the flocculation process. This cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
41
0

Year Published

1987
1987
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 16 publications
1
41
0
Order By: Relevance
“…The integral form of eq. [2] is This equation was successfully used for the kinetic study of the permanganate ion oxidation of dimethylamine (3) and trimethylamine (2) and was also proposed for the acid-catalyzed hydrolysis of esters (44).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The integral form of eq. [2] is This equation was successfully used for the kinetic study of the permanganate ion oxidation of dimethylamine (3) and trimethylamine (2) and was also proposed for the acid-catalyzed hydrolysis of esters (44).…”
Section: Resultsmentioning
confidence: 99%
“…[ l ] and [2] The values of the rate constants corresponding to different methylammonium ion concentrations have been determined. We can see in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This has given rise to the use of stabilization aids. Mata-Perez and PerezBenito [28] found that the conversion rate of soluble Mn(IV) to MnO 2 (s) could be delayed when phosphate was present. Kao et al [29] found that ~82% of MnO 2 production could be inhibited by including Na 2 HPO 4 with MnO 4 − without affecting TCE loss.…”
mentioning
confidence: 99%